Expression of Tight Junction Protein Claudin-1 in Human Crescentic Glomerulonephritis - Ryo Koda; Atsunori Yoshino; Yuji Imanishi; Shinya Kawamoto; Yoshihiko Ueda; Eishin Yaoita; Junichiro James Kazama; Ichiei Narita; Tetsuro Takeda (International Journal of Nephrology)
The origin of crescent forming cells in human glomerulonephritis (GN) remains unknown. Some animal studies demonstrated that parietal epithelial cells of Bowman’s capsule (PECs) were the main component of proliferating cells and PEC-specific tight junction protein claudin-1 was expressed in crescentic lesions. We investigated the expression of claudin-1 in human GN. Immunohistochemistry for claudin-1 was performed on 17 kidney biopsy samples with crescent formation. Colocalization of claudin-1 with intracellular tight junction protein ZO-1 was also evaluated by immunofluorescence double staining. Claudin-1 is expressed mainly at the cell to cell contact site of proliferating cells in cellular crescentic lesions in patients with these forms of human GN. Small numbers of crescent forming cells showed extrajunctional localization of claudin-1. Colocalization of claudin-1 with ZO-1 was found at cell to cell contact sites of adjacent proliferating cells. In control samples, staining of claudin-1 was positive in PECs, but not in podocytes. Our findings suggest that claudin-1 contributes to crescent formation as a component of the tight junction protein complex that includes ZO-1. Co-localization of claudin-1 with ZO-1 implies the formation of functional tight junction complexes in crescentic lesions to prevent the interstitial damage caused by penetration of filtered molecules from Bowman’s space.